Prevalence of Celiac Disease Amongst Patients with Chronic Diarrhea: A Cross Sectional Study - Naseeb Ur Rehman Shah, Samiullah Khan, Muhammad Omar Khan, Mohsin Ul Alam, Radhia Khan, Adan Razaq, Abdul Razaq (Pakistan Journal of Medical & Health Sciences, 2023)
Background: An autoimmune disease called celiac disease (CD) causes intolerance of gluten in genetically predisposed individuals. Celiac disease may exhibit a variety of clinical signs, making it difficult to diagnose based purely on symptoms. Objective: To find out the prevalence of celiac disease amongst chronic diarrhea patients Methodology: The current study was cross sectional carried out at the department of Medicine, Khalifa Gul Nawaz Teaching Hospital, Bannu Medical College Bannu from August 2022 to January 2023. All the laboratory examination like blood smear, stool routine examination serum calcium and serum albumin was done. The serological tests for celiac disease like IgA anti TTG and IgG anti TTG was also determined. All the data was documented in a proforma designed for this study. All the data collected was analyzed by employing IBM SPSS version 23. Results: Amongst total 140 patients, the male patients in our study were 67 (47.86%) whereas female patients were 73 (52.14%). The mean age (SD) in the current research was 34 (7.12) years. The overall celiac disease prevalence amongst chronic diarrhea patients was 18 (12.86%). Conclusion: Our study concludes that the prevalence of celiac disease amongst chronic diarrhea patients is very high. Keywords: Prevalence; celiac disease; chronic diarrhea